Teacher’s Opinion Regarding Potential use and Misuse of Teachers’ Evaluation in Undergraduate Dental Education (Bangladesh Journal of Medical Education, 2018)
Teachers' evaluation in our country is yet to be started. But in many countries of the world it has been adopted a long time ago. It not only affects the teaching process but also motivate teachers for self-development. It is a series of activities and actions that are interconnected and relate to a specific purpose. In the last two decades, the importance of teaching evaluation has been emphasized in higher education. Many medical and dental schools have searched for ways to effectively and constructively evaluate performances of their faculty members. This cross-sectional descriptive study conducted among the teachers of public & private dental colleges adopting convenience sampling. Study revealed that teacher evaluation can improve teacher's teaching ability (94.1%), it can be used to assessing training need of the teacher (94.1%), it can protect students from incompetent teachers (91.2%), it can be used for promoting teachers (91.2%), it can also help to monitor the performances of teacher by administrators (88.2%), The most common sources of evaluation data have been students, peers, and teachers themselves. Teacher evaluation is often designed to serve two purposes- to measure teacher competence and to foster professional development and growth. A teacher evaluation system give teachers useful feedback on classroom needs, the opportunity to learn new teaching techniques, and counsel from principals and other teachers on how to make changes in their classrooms. The goal of any effective evaluation process must be growth of good teacher.Bangladesh Journal of Medical Education Vol.9(2) 2018: 24-26